Packaging the product: A case study of verbal and non-verbal paratext in Chinese-English translation - Valerie Pellatt (JoSTrans: The Journal of Specialised Translation)
This paper argues that publishers and editors make certain assumptions about the readership of books and manipulate the translation and the readers by exploiting the non-verbal and verbal layout and presentation of paratextual elements. The term 'paratranslation' is used to denote the varied manifestations of translated paratext. The examples cited show how a publication is presented very differently to Chinese and non-Chinese readers. The article demonstrates how the domestic and anglophone audiences are targeted, and how a different message is sent across geo-political space. The second part of the paper focuses on one work, a memoir. The book jacket and blurb, the illustrations, the prefaces, postscripts, chapter headings, and the layout differ between the source text and the target text. The reasons for this can only be speculated upon, as there is no explicit justification from the publisher. However, the nature of the differences shows very clearly what motives the editor and/or the publisher may have in mind when creating what appears to be a different book. While in the end the reader reads a similar narrative, he or she is primed by the visual aspects of the publication to expect and receive a different message.